A novel approach to solve a mining work centralization problem in blockchain technologies. Issue 1 (3rd April 2018) - Kano, Yuki; Nakajima, Tatsuo
Abstract : Purpose: This paper aims to solve a mining work centralization problem using a gamification-based approach. Design/methodology/approach: The authors have developed a simple blockchain application that incorporates a gamification concept into the mining work. Then, they asked some participants in an experiment to use the application for a week and gathered some insights from the responses on questionnaires. Findings: The results show that the gamification-based approach distributed mining work among many participants by increasing their motivation to participate mining work. Originality/value: The gamification-based approach solves a mining work centralization problem and opens a new direction for future blockchain technologies.